(untitled) (Research, Society and Development, 2020)
The concern for healthy and nutritious food products is gaining more and more notoriety in the current scenario, and consequently becoming an object of study in the area of dairy manufacturers, highlighting the relevance of a diet supported by these products. The smoothie is a practical and healthy drink, since it has been a good way for the population to eat more fruits, without aggressive processes that are capable of damaging the main nutrients present in the fruit. In this work, smoothies will be prepared using fruit pulps (apple and banana) and milk fermented by kefir from different animal species (cow, sheep and goat). Thus, the objective of the experiment was to evaluate the physical-chemical, sensory and purchase intention of the formulated products. First, the ideal amount of each ingredient in the formulation was analyzed, taking into account the sensory and nutritional benefits of the product. The smoothie with goat’s milk fermented by kefir stood out for the highest percentage of votes in several aspects and the most positive purchase intention. Therefore, it is concluded that the production of smoothie with fermented milk of different species by kefir is viable, with variations in acceptance depending on the origin of the milk used.